Digital Era: Innovative Models and Diverse Pathways for Taijiquan Dissemination - Bai, Bingjie; Lu, Xiaofei (The Journal of the International Society of Chinese Health Practices, 2025)
Research Purpose: The rapid advance of digital technology is reshaping how Taijiquan is transmitted. This study explores innovative models and pluralistic pathways for Taijiquan dissemination in the digital age, addressing the limitations of traditional methods while capitalizing on new technological opportunities. Specific objectives are:(1) Analyze the current landscape and challenges of Taijiquan dissemination, pinpointing weaknesses in traditional models and emergent digital openings.(2) Probe innovative dissemination models—new-media platforms, virtual reality (VR), augmented reality (AR), and online education.(3) Construct diverse dissemination pathways targeting globalization, youth, and community audiences.(4) Validate these models and pathways through case studies, offering theoretical guidance and practical tools for the global promotion of Taijiquan. Research Methods: 2.1 Literature Review Asystematic review of domestic and international scholarship on Taijiquan transmission history, current status, and digital applications in sports-culture communication provided the theoretical foundation and identified research gaps. 2.2 Case Analysis Representative cases—e.g., Taijiquan on Douyin (TikTok) and the International Taijiquan Cultural Festival—were examined to reveal dissemination models, pathways, and measurable effects. 2.3 Field Investigation First-hand data were collected via questionnaires and interviews with Taijiquan masters, enthusiasts, online-platform users, and community residents to gauge acceptance of and demand for different dissemination modes. Research Findings: 3.1 Current Situation and Challenges Traditional modes (master–disciple transmission, offline classes) are constrained by limited reach, temporal–spatial restrictions, and uneven teaching resources. Digital technologies offer new opportunities—new-media convenience, immersive VR/AR experiences, and systematic online curricula—yet also pose challenges: information fragmentation, variable content quality, and unequal access to technology. 3.2 Innovative Dissemination Models New-media platforms (Douyin, WeChat Channels, etc.) exploit short-video virality and social interactivity to attract and retain users. VR/AR delivers immersive teaching through motion-capture and virtual scenes, enhancing both pedagogical efficacy and cultural experience. Purpose-built online platforms provide tiered, systematic curricula combining live and recorded sessions for personalized learning. 3.3 Diverse Dissemination Pathways Globalization: collaborate with international wushu federations, stage multicultural festivals, and develop multilingual teaching materials. Youth: introduce Taijiquan into schools, blend online/offline activities, and create youth-friendly content (animated forms, competitive mini-games).Community: establish neighborhood training spots, organize cultural events, and leverage community social-media accounts to amplify Taijiquan’s social presence.3.4 Case Validation Douyin analytics show that short videos and livestreams dramatically expand reach and user engagement. The International Taijiquan Cultural Festival demonstrates how hybrid online–offline events magnify impact and foster cross-cultural exchange. Both cases corroborate the effectiveness of the proposed models and pathways. Conclusion: 4.1 Necessity and Opportunity The digital era offers unprecedented opportunities; innovative models and diverse pathways are essential to overcome traditional limitations. New-media platforms, VR/AR, and online education can transcend temporal and spatial constraints, enhancing dissemination efficiency. 4.2 Effectiveness of the Proposed Models and Pathways Empirical evidence confirms that the innovative models (new-media, VR/AR, online platforms) and the three pathway dimensions (global, youth, community) significantly widen reach, boost interactivity, improve content quality, and facilitate cultural exchange. 4.3 Future Outlook Future work should deepen the integration of digital technologies—e.g., AI-powered intelligent tutoring systems—strengthen international cooperation for global diffusion, and sustain attention on youth and community segments through diversified pathways, ensuring the long-term viability of Taijiquan in the digital age.